Systemically important company identification based on topological characteristics of the common share pledge network - Yuyin Ma; Qiong Sun; Chao Wang (Frontiers in Physics)
IntroductionWith the continuous development of the global securities market, share pledges as a business form are gradually emerging. However, there are also certain risks associated with share pledges. There are many common pledges between different share pledgers, which may result in financial contagion.MethodsThis paper constructs a common share pledge network and proposes an identification method of systemically important listed companies by analyzing the characteristics of its network structure, to improve the stability of the financial market.ResultsThe results show that the share pledges are concentrated in a certain number of large companies, exhibiting scale-free characteristics and multiple local community features. The supervision of share pledges will promote the formation of such characteristics. Although financial supervision reduces the probability of share pledge risks, it also improves the importance of companies with high centrality in the share pledge market.DiscussionCompared with the traditional network characteristics the centrality of the common share pledge network will provide more information about the share pledge risk. Different characteristics of network centrality can effectively identify systemically important companies, which has important regulatory value for financial risk prevention.